Optimasi Formula Stick Balm Minyak Atsiri Daun Sereh (Cymbopogon citratus) - I Komang Ary Werdhi Widnyana; Nisa Isneni Hanifa; Windah Anugrah Subaidah (Lembaga Penelitian Sekolah Tinggi Ilmu Farmasi Jl. Kamboja Simpang Baru-Panam, Pekanbaru, Riau 28293 Telp. (0761) 588006, Fax. (0761) 588007 e-mail: editor-jpfi@stifar-riau.ac.id, 2021)
The content in lemongrass leaves essential oil (Cymbopogon citratus) has a neurobehavioral effect, so lemongrass leaves essential oil can be useful as aromatherapy. The stick balm form as an innovation of aromatherapy form is required to increase the user’s comfort and ease of application of the product. The aim of this study is to determine the optimum formula and physical properties of lemongrass essential oil stick balm form with additive variations of cera alba and lanolin. Eight stick balm formula designs were determined by using SLD (Simplex Lattice Design), method with Design Expert 11 software, and made by using melting method. The stick balm forms were tested for the physical properties such as pH test, melting point test, and adhesion test. The response to the physical properties test was processed by using Design Expert 11 software to obtain optimal formula. The optimal form of stick balm was tested for physical, organoleptic, and homogeneity properties. The results of the physical properties test of optimal formula were verified by using one sample t-test method with SPSS software. The results of the optimization of the formula were 5,310% of lanolin and 11,690% of cera alba. The stick balm forms were bright yellow in color, have a characteristic smell of lemongrass essential oil, semi-solid consistency, homogeneous mixed materials, pH level of 5,63±0,06, melting point of 44,5±0,5oC, and adhesion tests of 2,437±0,106 seconds, with the result that, the optimum formula of stick balm met requirements for the physical properties. The physical properties of the optimal formula are not significantly different from the predictions in the Design Expert 11 application.